Utilization of Technological Literacy to Improve Students' Critical Thinking Skills in Writing Text - Hasibuan, Mutiara Sany; Lubis, M. Joharis; Hutagalung, Surya Masniari (PT. Riset Press International, 2025)
In the digital era, technological literacy is an essential skill that needs to be mastered by students to face the challenges of the 21st century. This study analyzes how technological literacy can improve students' critical thinking skills in writing texts. The method used is classroom action research (PTK) involving 30 class XI MPLB 6 students at SMK Negeri 7 Medan. The learning process utilized various technology platforms, such as word-processing software, online collaborative tools, and interactive learning applications. The results showed that technological literacy significantly improved students' critical thinking skills, particularly in identifying arguments, analyzing text structure, and composing coherent and logical writing. In addition, students also became more independent in evaluating and revising their texts with the help of digital tools.